Sustainable Lighting & Lighting for Sustainability (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The role of lighting is developing into a topic considered alongside sustainable development. Some years ago, lighting installations fulfilled technical requirements and consumed only enough energy for the accurate completion of visual tasks. This recently changed due to several discoveries in the matter of non-visual paths, whose influence on users' well-being, safety, mood, and productivity is starting to be applied to installations. Today, we know that sustainable development depends on many factors but we are only now beginning to understand how accurate lighting can be used to promote development from different perspectives. The present book compiles work dealing with the way lighting installations must be designed to work in an efficient and sustainable way, together with the way lighting can be used to contribute to sustainable development beyond the well-know savings in energy, green-house gas emissions, and raw materials consumption. The union of both concepts, sustainable lighting and lighting for sustainability is what is call "total lighting", the global framework with which the lighting community will work in the near future.